W.L. Cook papers - Cook, W. L.
Court records consisting of a copy of Cook's transcription of the shorthand notes of his predecessor, Adam Patterson, court stenographer in the two trials of John D. Lee. The trials, held in Utah in 1875-1876, are concerned with Lee's and other Mormons's alleged complicity in the 1857 massacre of Arkansas emigrants at Mountain Meadow, Utah.
Court stenographer.
Collection material in English.
Keywords: Lee, John D; Patterson, Adam; Courts -- Utah; Mormon Church; Mormons; Mountain Meadow (Utah); Stenographers